REPRESENTASI GENERASI SANDWICH PADA FILM HOME SWEET LOAN SEMIOTIKA ROLAND BARTHES - Syaira Amanda Putri; Silvina Mayasari; Sari Ekowati Hadi (An Nafi': Multidisciplinary Science, 2025)
This study examines the representation of the sandwich generation phenomenon in the film "Home Sweet Loan" (2024), an issue that is increasingly relevant in modern Indonesian society, as evidenced by the high number of Gen Z who feel financial and emotional burdens due to dual responsibilities. Film as a significant mass communication media is able to reflect social reality and has the potential to change mindsets. The purpose of this study is to understand how the sandwich generation is represented in the film's visual narrative. Using a qualitative approach with Roland Barthes' semiotic analysis design and constructivism paradigm, this study analyzes key scenes in the film in depth. The results show that the film "Home Sweet Loan" explicitly depicts the physical, mental, and financial pressures faced by sandwich generation individuals, such as the character Kaluna who sacrifices her personal dreams for the sake of family needs and debts. Roland Barthes' semiotic analysis successfully reveals the layers of denotative, connotative, and mythical meaning behind each scene, showing the injustice, sacrifice, and feeling of being trapped experienced by this generation. In conclusion, this film successfully presents a comprehensive picture of the challenges of the sandwich generation, encouraging reflection on roles and responsibilities within the family.